Nonvolatile current-induced topological charge imbalance of magnetic textures - Shangyuan Wang; Lei Qiu; Ka Shen (Communications Physics)
Abstract The topological charge of magnetic solitons gives rise to characteristic Hall-type effects, which allows to recognize the nontrivial topology of the spin textures, such as skyrmions or antiskyrmions. The selective manipulation of topological magnetic textures with different topological charges could substantially enrich potential applications but remains largely elusive. Here, we report an electrical control of net topological charge in a magnetic film hosting both skyrmions and antiskyrmions at finite magnetic field or bimerons and antibimerons at zero field, where their distinct responses to the current-induced torques result in a nonvolatile imbalance between the two oppositely charged topological textures. Both the magnitude and the sign of the resulting topological charge are found to be controllable efficiently by adjusting the orientation of the driving current with and without magnetic field. Our findings open the way to the on-demand manipulation of topological spin textures and provide more opportunities for designing spin-texture-based multifunctional devices.